1996
DOI: 10.1159/000246401
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Herpes simplex Virus in Exacerbated Pemphigus vulgaris by Polymerase Chain Reaction

Abstract: Background: Herpes simplex virus infections are well known complications of various dermatoses and have also been reported in acantholytic diseases like pemphigus vulgaris or Darier’s and Hailey-Hailey diseases. In pemphigus vulgaris, herpes simplex virus infection is considered to be rare and difficult to rule out clinically. Objective: We report on 3 patients suffering from pemphigus vulgaris with exacerbation especially of lesions of the oral mucosa. Methods and Results: While conventional techniques failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
1
29
0
2
Order By: Relevance
“…SCHLUPEN et al 23 have described three cases of pemphigus with mucosal exacerbation, which have failed with immunosuppressive therapy and have only succeeded after the addition of antiviral treatment. In those cases, DNA of HSV has been demonstrated in research with PCR in the lesions.…”
Section: Krainmentioning
confidence: 99%
“…SCHLUPEN et al 23 have described three cases of pemphigus with mucosal exacerbation, which have failed with immunosuppressive therapy and have only succeeded after the addition of antiviral treatment. In those cases, DNA of HSV has been demonstrated in research with PCR in the lesions.…”
Section: Krainmentioning
confidence: 99%
“…Schlupen et al reported 3 patients suffering from pemphigus vulgaris had exacerbation of oral mucosal lesion due to secondary herpes virus infection [6]. Tufano et al have investigated the presence of various infections including herpes virus 1/2, EBV, CMV, and HHV-6 in 20 patients with pemphigus using serology and PCR in peripheral blood mononuclear cells (PBMC) and also in biopsy samples.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies suggested that herpesviruses could trigger PV progression [2,3,7,8,9]. In addition, other studies have suggested that herpesvirus infections represented a complication of pemphigus resulting from immunosuppressive therapies and/or a causative factor associated with treatment-resistant lesions [6,10,12,13,14,15,16,17,22,23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…HSV infections are often identified in association with recurrent/persistent PV lesions in patients already undergoing corticosteroid treatment. In most cases, HSV diagnosis was delayed for several months, because viral lesions mimicked PV lesions [12,22,25,26]. However, when the HSV diagnosis was established and the treatment was initiated, the lesions cleared promptly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation